Stability analysis and application of a mathematical cholera model - Shu Liao; Jin Wang (Mathematical Biosciences and Engineering)
In this paper, we conduct a dynamical analysis ofthe deterministic cholera modelproposed in [9]. We study the stability of both thedisease-free and endemic equilibria so as toexplore the complex epidemic and endemic dynamics of the disease.We demonstrate a real-world application of this model byinvestigating the recent cholera outbreak in Zimbabwe. Meanwhile,we present numerical simulation results to verify theanalytical predictions.